2011
DOI: 10.1590/s1413-70542011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de soro de queijo no processo de obtenção de etanol a partir de batata-doce

Abstract: Estudou-se o incremento na produção convencional de etanol de batata-doce [Ipomoea batatas (L.) Lam.] incorporando soro de queijo ao processo e a variação nos teores de proteína bruta dos resíduos sólidos úmidos gerados por esses processos utilizando-se dois cultivares selecionados no estado do Tocantins. O incremento na produção convencional de álcool de batata-doce alcançou um porcentual de 16,6% quando o soro de queijo hidrolisado foi incorporado ao processo, resumidos em até 28,9 litros a mais de etanol po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
0
1
2
Order By: Relevance
“…The group consisting of the clones IPB-014, IPB-075, IPB-079, IPB-137, and IPB-139 and the control Brazlândia Rosada presented the highest mean value for EY (Table 4 (Table 4). For the municipalities of São Cristóvão and Malhador, results were similar to those found by Castro et al (2011), who obtained SY values of 46.7 T ha -1 and 32.17 T ha -1 , and EY values of 9545.48 L ha -1 and 6866.68 L ha -1 , for the cultivars Amanda and Carolina Vitoria, respectively. However, when comparing the results of the same study with the values found in Canindé de São Francisco, in the present study, the latter exhibited higher values than those found by Castro et al (2011) (EY values higher than 10000 L ha -1 ).…”
Section: Ethanol Yield (Ey)supporting
confidence: 87%
See 1 more Smart Citation
“…The group consisting of the clones IPB-014, IPB-075, IPB-079, IPB-137, and IPB-139 and the control Brazlândia Rosada presented the highest mean value for EY (Table 4 (Table 4). For the municipalities of São Cristóvão and Malhador, results were similar to those found by Castro et al (2011), who obtained SY values of 46.7 T ha -1 and 32.17 T ha -1 , and EY values of 9545.48 L ha -1 and 6866.68 L ha -1 , for the cultivars Amanda and Carolina Vitoria, respectively. However, when comparing the results of the same study with the values found in Canindé de São Francisco, in the present study, the latter exhibited higher values than those found by Castro et al (2011) (EY values higher than 10000 L ha -1 ).…”
Section: Ethanol Yield (Ey)supporting
confidence: 87%
“…For the other four groups, mean SY values varied between 2.59 T ha -1 and 9.34 T ha -1 (Table 3). SY values found in the three municipalities were lower than those obtained by Silveira (2004), using cultivar Carolina Vitoria (22.55 T ha -1 ); and by Castro et al (2011), using cultivar Amanda (30.17 T ha -1 ).…”
contrasting
confidence: 68%
“…Os ensaios que seguem 0,7%/60 minutos; 0,7%/90 minutos; 1%/30 minutos; 1%/60 minutos e 1%/90 minutos também alcançaram a taxa de hidrólise desejada, porém, evidenciam um maior consumo de tempo ou enzima. Castro et al (2011) realizaram ensaios de hidrólise da lactose de soro de queijo com a lactase β-galactosidase de K. lactis (Maxilact ® LX-5000) e verificaram que os maiores pontos de hidrólise da lactose foram obtidos nas concentrações enzimáticas de 0,2% (m/v) e 0,7% (m/v) a temperatura de 37 ºC e pH 6,5 por 50 minutos. Vieira (2006) realizou ensaios enzimáticos com a lactase (β-galactosidase) de K. lactis da marca Prozin ® em soro em pó re constituído com concentração de lactose de 75%, mantendo a concentração de 0,4% nas temperaturas de 43 ºC, 45 ºC, 48 ºC e 53 ºC nos pH 6,0 e 6,5.…”
Section: Ensaios De Hidrólise Da Lactose Com Permeadounclassified
“…Nesta vertente se observa que a indústria de alimentos produz uma série de resíduos com alto valor de reutilização (Castro et al, 2011;Pinho e t al., 2011;Barana et al, 2012). Inúmeros estudos utilizando resíduos agroindustriais têm sido realizados com o objetivo de minimizar o impacto ambiental das indústrias desenvolvendo alternativas de valorização de resíduos agroindustriais e de agregar valor aos produtos de mercado (Pelizer et al, 2007;Soares Júnior et al, 2011;Lima, 2011;Vilhalva et al, 2011;Sena et al, 2012;Castiglioni et al, 2013;Souza et al, 2013a,b;Sousa et al, 2013, Fiorda et al, 2013 Nas últimas duas décadas a indústria de processamento de batata vem ganhando espaço no cenário brasileiro abastecendo principalmente, o mercado de fastfood.…”
Section: Introductionunclassified